Regulatory Chaperone Complexes in Neurodegenerative Diseases: A Perspective on Therapeutic Intervention - Carman, Aaron; Kishinevsky, Sarah; Koren III, John; Luo, Wenjie; Chiosis, Gabriela (Current Alzheimer Research, 2014)
Protein folding, protein degradation, and protein stability are regulated by the molecular chaperones. Under pathogenic conditions, aberrant proteins can be dysfunctional, unregulated, or pathogenically mutated. These aberrant proteins are triaged by the chaperone network for the maintenance of cellular homeostasis. These species, called chaperone client proteins, include the pathogenic factors of numerous neurodegenerative disorders, including tau in Alzheimer’s disease, α-synuclein and LRRK2 in Parkinson’s disease, SOD-1, TDP-43 and FUS in amyotrophic lateral sclerosis, and polyQ-expanded proteins such as huntingtin in Huntington’s disease. In depth study of two molecular chaperones, Hsp90 and Hsc70, has led to a greater understanding of aberrant client fate and how retarding the chaperone system can promote clearance of these pathogenic clients. Here we discuss how chaperone interactions and small molecule inhibitors can regulate the burden of aberrant client signaling in these neurological disorders.
Keywords: molecular chaperones